Antioxidant properties of red raspberry extract alleviate hepatic fibrosis via inducing apoptosis and transdifferentiation of activated hepatic stellate cells - Tung-Ho Wu (Elsevier, 2021)
Hepatic fibrosis is a wound-healing process caused by prolonged liver damage and often occurs due to hepatic stellate cell activation in response to reactive oxygen species (ROS). Red raspberry has been found to attenuate oxidative stress, mainly because it is rich in bioactive components. In the current study, we investigated the inhibitory effects and associated molecular mechanisms of red raspberry extract (RBE) upon activated hepatic stellate cell (aHSC) in cellular and rat models. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were increased in the dimethylnitrosamine (DMN)-applied samples, whereas treatment of RBE significantly suppressed the activities of these enzymes. In addition, a histopathological analysis demonstrated that RBE could substantially diminish the hepatic collagen content and alpha-smooth muscle actin (α-SMA) expression induced by DMN. Administration of 250 μg/mL RBE could also arrest the growth and enhance the apoptosis of activated HSC-T6 cells, which was accompanied with elevated levels of activated caspases and poly (ADP-ribose) polymerase (PARP) cleavage. Particularly, RBE application remarkably abolished oxidative damage within the cells and reduced the carbonylation of proteins, which was attributed to the upregulation of catalase, nuclear factor erythroid 2-related factor 2 (Nrf2), and heme oxygenase-1 (HO-1). Moreover, the knockdown of Nrf2 together with the RBE treatment synergistically abrogated the expression of α-SMA and promoted the level of peroxisome proliferator-activated receptor gamma (PPAR-γ), suggesting that RBE could mitigate the transdifferentiation of HSC in a Nrf2-independent manner. These findings implied that the application of RBE could effectively remove oxidative stress and relieve the activation of HSC via modulating the caspase/PARP, Nrf2/HO-1 and PPAR-γ pathways, which may allow the development of novel therapeutic strategies against chemical-caused liver fibrogenesis.